Inclusion in advertising to connect with the consumer - La-Jara, Nicole (2024)
Today’s consumers are more aware of what is happening in their social environment. Therefore, brands are adapting to these new consumer needs that lead to the romanticization of advertising strategies. The objective of this study is to identify the emotions felt by mothers in the inclusive discourse of Milo’s “Together in this back to school” campaign for the generation of awareness and loyalty. Its paradigm and design is phenomenological. The sampling was by snowball. Semi-structured interviews were conducted with twenty women mothers between the ages of 23 and 40. As a result, the use of inclusive discourse in advertising produced positive emotions such as “tenderness” and “emotion”. As a conclusion, if a brand works with social values and uses an inclusive discourse, it can achieve greater consumer acceptance and a change in their behavior towards the brand.